Effects of Resistance Exercise on Slow-Twitch Soleus Muscle of Infarcted Rats - Souza, Lidiane Moreira [UNESP] (2023)
Although current guidelines recommend resistance exercise in combination with aerobic training to increase muscle strength and prevent skeletal muscle loss during cardiac remodeling, its effects are not clear. In this study, we evaluated the effects of resistance training on cardiac remodeling and the soleus muscle in long-term myocardial infarction (MI) rats. Methods: Three months after MI induction, male Wistar rats were assigned to Sham (n = 14), MI (n = 9), and resistance exercised MI (R-MI, n = 13) groups. The rats trained three times a week for 12 weeks on a climbing ladder. An echocardiogram was performed before and after training. Protein expression of the insulin-like growth factor (IGF)-1/protein kinase B (Akt)/rapamycin target complex (mTOR) pathway was analyzed by Western blot. Results: Mortality rate was higher in MI than Sham; in the R-MI group, mortality rate was between that in MI and Sham and did not differ significantly from either group. Exercise increased maximal load capacity without changing cardiac structure and left ventricular function in infarcted rats. Infarction size did not differ between infarcted groups. Catalase activity was lower in MI than Sham and glutathione peroxidase lower in MI than Sham and R-MI. Protein expression of p70S6K was lower in MI than Sham and p-FoxO3 was lower in MI than Sham and R-MI. Energy metabolism did not differ between groups, except for higher phosphofrutokinase activity in R-MI than MI. Conclusion: Resistance exercise is safe and increases muscle strength regardless structural and functional cardiac changes in myocardial-infarcted rats. This exercise modality attenuates soleus glycolytic metabolism changes and improves the expression of proteins required for protein turnover and antioxidant response.